2004
DOI: 10.1111/j.0021-8901.2004.00915.x
|View full text |Cite
|
Sign up to set email alerts
|

On the loss of saltmarshes in south‐east England and methods for their restoration

Abstract: Summary1. The saltmarshes of south-east England have been eroding rapidly for about the last 50 years, at a continuing rate of about 40 ha year − 1 , with deleterious consequences for conservation and coastal flood defence. The possible reasons for this erosion and suitability of methods of saltmarsh restoration are discussed. 2. The prevailing hypothesis that the saltmarsh erosion is due to coastal squeeze, where sea walls prevent a landward migration of saltmarsh in response to sea level rise, is rejected be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 35 publications
(52 reference statements)
1
71
1
1
Order By: Relevance
“…Surprisingly, however, these papers neglect the potential restoration benefits of the removal of negative interactions originating from ecosystem engineers, despite the fact that such interactions can play an important role in marine habitats (Rhoads and Young 1970, Philippart 1994, Hughes et al 2000, Hughes and Paramor 2004, Siebert and Branch 2006, Berkenbusch et al 2007, van Wesenbeeck et al 2007. In this study, we show that suppressing such negative ecosystem-engineering effects could be a useful approach in restoration and conservation efforts by giving at least a better start during the initial establishment phase.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Surprisingly, however, these papers neglect the potential restoration benefits of the removal of negative interactions originating from ecosystem engineers, despite the fact that such interactions can play an important role in marine habitats (Rhoads and Young 1970, Philippart 1994, Hughes et al 2000, Hughes and Paramor 2004, Siebert and Branch 2006, Berkenbusch et al 2007, van Wesenbeeck et al 2007. In this study, we show that suppressing such negative ecosystem-engineering effects could be a useful approach in restoration and conservation efforts by giving at least a better start during the initial establishment phase.…”
Section: Discussionmentioning
confidence: 65%
“…For example, this has been shown for the negative effect of deposit feeders on filter feeders by making sediment more erosive, causing filter feeding to be hampered by more turbid water (i.e., trophic group amensalism; Rhoads and Young 1970). Several studies have also demonstrated that negative interactions between benthos and vegetation can be very strong (Philippart 1994, Hughes et al 2000, Hughes and Paramor 2004, Siebert and Branch 2006, Berkenbusch et al 2007, van Wesenbeeck et al 2007). For instance, ''biomechanical warfare'' between ecosystem-engineering salt marsh vegetation and infauna can cause a bimodal species distribution on the salt marsh-mudflat interface, as bioturbation prevented plant colonization in the invertebrate-dominated state and invertebrates were excluded by sediment compaction in the plantdominated state (van Wesenbeeck et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The overall management implication of a coastal wetland, if validated to comply with multiple stable state theory, would be that the wetland is valuable and long-lived, but non-stationary, and once degraded very difficult to restore. In fact, high rates of failure in coastal wetland restorations already suggests such a case [46][47][48][49].…”
Section: Invoking Multiple Stable State Theorymentioning
confidence: 99%
“…Other herbaceous wetlands subject to transplanting are declining coastal marshes (e.g., Bakker et al 1997, Hughes andParamor 2004). On the west coast of North America, plugs supporting five dominant marsh species were planted on constructed islands in an attempt to produce marshes like the natural ones that had been lost.…”
Section: Translocation Of Entire Communitiesmentioning
confidence: 99%